Precipitable water characterization using global navigation satellite system data: A case study in Nghia Do area, Vietnam - Pham Le, Khuong; Nguyen Xuan, Anh; Van Nguyen, Hiep; Hoang Hai, Son; Nguyen Nhu, Vinh; Bui Ngoc, Minh (Vietnam Journal of Earth Sciences, 2024)
This paper evaluates the estimated total precipitable water (TPW) and studies its characteristics in the Nghia Do area (Hanoi) using Global Positioning System (GPS) data and the Canadian Spatial Reference System-Precise Point Positioning (CSRS-PPP) processing technique and calculation tool. The TPW was estimated from GPS data from September 22, 2022 to March 31, 2023 using CSRS-PPP provided by Natural Resources Canada. The calculated TPW was validated with TPW products from Aeronet data and radiosonde data. Taking advantage of its high time resolution, the TPW estimated from GPS data was used to analyze the temporal variation of TPW during cold surges affecting the Nghia Do area. The results indicate a strong agreement between the estimated TPW from GPS data and TPW products derived from Aeronet and radiosonde data. The mean error (ME), root mean square error (RMSE), and correlation coefficient between the estimated TPW from GPS data and the Aeronet-derived product are 0.68 mm, 2.05 mm, and 0.988, respectively. The corresponding values between the estimated TPW and the radiosonde-derived product are -3.01 mm, 3.24 mm, and 0.996, respectively. The study of TPW variation over the Nghia Do area during the research period revealed that, generally, TPW values in December and January were lower than those in the other months. Before the arrival of a specific cold surge at a station, TPW tends to increase by about 6 mm within 12 hours as convection activities ahead of the cold front intensify. After the cold air passes over the station, the TPW value decreases by about 8 mm within 12 hours due to the influx of cold and dry winter air brought by the prevailing winds. This distinct TPW variation pattern suggests that GPS data can be effectively employed to define the arrival of cold surges in the station area.